2022
DOI: 10.3390/ejihpe12060044
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Therapeutic Exercise in Musculoskeletal Risk Factors Related to Swimmer’s Shoulder

Abstract: Background: Therapeutic exercise seems to minimize musculoskeletal risk factors related to swimmer’s shoulder. However, there is an absence of a qualitative evaluation of these programs and a great variability regarding the characteristics of exercises. The objective of this review was to identify, evaluate, and compare exercise programs used to minimize musculoskeletal risk factors related to swimmer’s shoulder. Methods: PubMed, CochraneLibrary, ScienceDirect, and Medscape were searched during January 2022. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Tavares., who reported that the proposed rehabilitation programs with their content, whether (equipment or tools), which consider individual differences among swimmers, had a positive and statistically significant effect between the pre-and post-measurements of the experimental group in favor of the post-measurement in developing flexibility, whether toward extension or flexion. Positive for swimmers and increased shoulder joint range of motion [34,35].…”
Section: Presentation and Discussion Of The Resultsmentioning
confidence: 99%
“…Tavares., who reported that the proposed rehabilitation programs with their content, whether (equipment or tools), which consider individual differences among swimmers, had a positive and statistically significant effect between the pre-and post-measurements of the experimental group in favor of the post-measurement in developing flexibility, whether toward extension or flexion. Positive for swimmers and increased shoulder joint range of motion [34,35].…”
Section: Presentation and Discussion Of The Resultsmentioning
confidence: 99%
“…There are some exercises that seem to prevent shoulder pain. Some authors propose specific preventative protocols [52,53].…”
Section: Discussionmentioning
confidence: 99%